DE L’INTERMÉDIAIRE DANS LA PHILOSOPHIE DE L’ESPACE : PRÉCARITÉ, CRÉATION, LIBERTÉ - MIHALI, Ciprian (Studia Universitatis Babeș-Bolyai Philosophia, 2022)
The Intermediary in the Philosophy of Space: Precariousness, Creation, Freedom. The reflection proposed by this text is the result of a dialogue spread over several years between philosophers and geographers. The best common ground between each other – in the right middle of the road – is undoubtedly the concept of the intermediary, which describes, negatively or affirmatively, the future of our physical, social, conceptual spaces and which speaks to us about discontinuity, hybridization, flow, contiguity, but also vulnerability, counterpowers and freedom. We wanted to show that far from being a concept of the residual, the unassimilable, the incomprehensible or even the irrational, the intermediary is the place of hospitality, the open work of alternative creativity, resistance, or affirmation of those who, excluded from dominant discourses, claim a right to speak and freely participate in social life.